1976
DOI: 10.1016/s0022-5347(17)59060-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary Adenovillous Carcinoma of the Bladder

Abstract: Two cases of primary adenovillous carcinoma of the bladder are presented: one in a normally placed bladder and the other in an exstrophied bladder. The close association of these 2 neoplasms with coexistent cystitis glandularis would seem to support the possible precancerous nature of the latter entity. The remarkable similarity of these neoplasms to villous adenocarcinomas of the rectum is also described, a finding which may reflect the close embryologic origin of the rectum and bladder neck. A brief review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
3

Year Published

1981
1981
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 23 publications
0
13
0
3
Order By: Relevance
“…The former does not have the well‐formed villous structures that are typical of the villous adenoma. In the latter, the epithelium is pseudostratified, and the nuclei are enlarged, crowded and hyperchromatic, features that are not present in cystitis glandularis 8 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The former does not have the well‐formed villous structures that are typical of the villous adenoma. In the latter, the epithelium is pseudostratified, and the nuclei are enlarged, crowded and hyperchromatic, features that are not present in cystitis glandularis 8 …”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of glandular metaplasia with invasive adenocarcinoma of the urothelium is a frequent finding. Therefore, it has been suggested that glandular metaplasia (cystitis glandularis), in some cases, might evolve into adenocarcinoma 8,9 . However, at least one study did not confirm that intestinal metaplasia was a strong risk factor for the development of a malignant neoplasm of the urinary bladder 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 "Malignant transformation of a urachal villous adenoma is a possible mechanism for the histogenesis of primary adenocarcinoma of the bladder" Villous adenoma is rarely found outside the large bowel, and villous glandular neoplasms are uncommon in the urinary bladder. [3][4][5][6][7][8][9] Urachal villous adenoma is very rare. In the report by Eble et al, 7 16 cases were identified in the literature published up to 1986.…”
mentioning
confidence: 99%
“…These included an intravesical suture, a urethral diverticulum, 2 cases of papillary transitional-cell carcinoma and 2 cases of cystitis glandularis. Cystitis glandularis is a glandular metaplasia associated with chronic irritation of the bladder mucosa and adenovillous carcinoma, and is a possible precursor of the latter [9][10][11].…”
Section: Resultsmentioning
confidence: 99%